The European Hernia Society Prehabilitation Project: A Systematic Review of Intra-Operative Prevention Strategies for Surgical Site Occurrences in Ventral Hernia Surgery - Wouters, D.; Cavallaro, G.; Jensen, Kristian K.; East, B.; Jíšová, B.; Jorgensen, L. N.; López-Cano, M.; Rodrigues-Gonçalves, V.; Stabilini, C.; Berrevoet, F. (Frontiers in Surgery, 2022)
Background: Ventral hernia repair is one of the most commonly performed surgical procedures worldwide. To reduce the risk of complications, pre- and intra-operative strategies have received increasing focus in recent years. To assess possible preventive surgical strategies, this European Hernia Society endorsed project was launched. The aim of this review was to evaluate the current literature focusing on pre- and intra-operative strategies for surgical site infection (SSI) and surgical site occurrences (SSO) in ventral hernia repair. Methods: A systematic review was conducted and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Databases used were Pubmed and Web of Science. Original retrospective or prospective human adult studies describing at least one intra-operative intervention to reduce SSI/SSO after ventral hernia repair were considered eligible. Results: From a total of 4775 results, a total of 18 papers were considered suitable after full text reading. Prehospital chlorhexidine gluconate (CHG) scrub appears to increase the risk of SSO in patients undergoing ventral hernia repair, while there is no association between any type of surgical hat worn and the incidence of postoperative wound events. Intraoperative measures as prophylactic negative pressure therapy, surgical drain placement and the use of quilt sutures seem beneficial for decreasing the number of SSI and/or SSO. No positive effect has been shown for antibiotic soaking of a synthetic mesh, nor for the use of fibrin sealants. Conclusion: This review identified a limited amount of literature describing specific preventive measures and techniques during ventral hernia repair. An advantage of prophylactic negative pressure therapy in prevention of SSI was observed, but different tools to decrease SSIs and SSOs continuously further need our full attention to improve our patient outcomes and to lower overall costs.